Possible observation of horizontal roll vortices over the Adriatic Sea during bora - Belusic, Danijel; Vecenaj, Zeljko; LeMone, Margaret A. (Frontiers in Earth Science, 2015)
We report a possible occurrence of horizontal roll vortices over the Adriatic Sea during the bora wind. The National Center for Atmospheric Research Electra aircraft measured the turbulence structure above the Adriatic on 07 November 1999 during the Mesoscale Alpine Program. The data indicate that horizontal roll vortices are generated by the strong cold-air outbreak associated with bora. The rolls have a horizontal wavelength of about 1 km and an aspect ratio of approximately 1.5. There is no indication of the presence of cloud streets typically associated with the rolls, which is a consequence of the dry air advection in the lower troposphere resulting from the downslope flow.